KARAKTERISTIK HABITAT PREFERENSIAL TARSIUS (Tarsius fuscus) DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Abdul Haris Mustari; Nur Aisyah Amnur; Agus Priyono Kartono (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Tarsius fuscus was reported to occur in Bantimurung Bulusaraung National Park and its adjacent areas. For effective conservation, a detailed knowledge of the habitat requirements and preferences of the species is needed. The presence of Tarsius fuscus population and its habitat characteristics in Bantimurung Bulusaraung National Park are not clearly known. The habitat quality and space have been decreasing due to the increasing human activities. This study was carried out in Bantimurung Bulusaraung National Park at three different sites including Pute, Parang Tembo and Pattunuang forest blocks from Desember 2009 to Pebruari 2010. This study aimed to analyze the relationship between the existence of Tarsius fuscus and its habitat characteristics, and to determine habitat preferences of Tarsius fuscus in the study area. The results showed that Tarsius fuscus was found at 75 m – 360 masl from flat to steep topography with slope gradient varied from 0% to 25%. Plant diversity was significantly different in each location, with the highest density was in Pute. Based on the Neu Index Parang Tembo was more preferred than two other habitats. The distribution patterns of insects at the three different habitats were clumped, yet abundance of insects was highest in Pattunuang. Keyword: habitat characteristics, habitat preferences, Tarsius fuscus